Improved Intersection Design And Monitoring In The Sydney Coalfield - G. R. Corbett (International Conference on Ground Control in Mining, 1995)
The introduction of roof bolts to Phalen Colliery in the Sydney Coalfield, Nova Scotia (annual output of 2Mt) has been successfully implemented in maingate and tailgate entries over the last four years. Monitoring of the roof bolted areas continues to be an integral part of the quality control program as the results are utilized to maintain safety and to aid in long-term design strategies. Although all gateroads in the Phalen Colliery have converted to roof bolts as their primary means of support, the majority of intersections which intersect the main slopes remain supported by large steel structures. Several intersections within the Phalen Colliery were monitored as they were created by the mining process. A comparison is made between intersections supported with only traditional 6.4 to 6.7 m steel structure and intersections supported by 2.44 m fully resin encapsulated roof bolts in conjunction with 7.6 m fully cement grouted cable bolts. Detailed monitoring was conducted using CA NM ET's intrinsically safe sonic probe extensometer datalogger which has the ability to read up to sixteen probes simultaneously at programmed intervals. The density of the data from the datalogger has allowed a better understanding of the deformation of cable bolted intersections than was possible with manual monitoring. Test results have helped mine operators to design safer cable bolted intersections.